Emergence of and Risk Factors for Ciprofloxacin-Gentamicin-Resistant Escherichia coli Urinary Tract Infections in a Region of Quebec - Jacques Pépin; Mireille Plamondon; Caroline Lacroix; Isabelle Alarie (Canadian Journal of Infectious Diseases and Medical Microbiology, 2009)
BACKGROUND: An increased incidence of urinary tract infections (UTIs) caused by ciprofloxacin-gentamicin-resistant Escherichia coli (CiGREC) has been observed in a tertiary care centre in Sherbrooke, Quebec. The risk factors for such infections remained unclear.